Determination of the serum antibody level of different age groups of broiler chicken against Infectious Bursal Disease (IBD) - Hossain, MI; Nath, BK; Prodhan, MAM (International Journal of Natural Sciences, 2016)
A study on Infectious Bursal Disease (IBD) was conducted on broiler chicks (N=200+70) of strains: Cobb-500 and Hubbard classic at Laxmipur district of Bangladesh. The blood sample were collected at day old chicks (1st day), pre-vaccinated flocks (11th day) and post-vaccinated flocks (26th day), to measure the antibody titer by indirect ELISA method. Maternal derived antibody (MDA) mean titer of day old chicks (N=40) were found 9621.65 ± 780.78 and 4232.60 ± 301.66 for Cobb-500 and Hubbard classic respectively. MDA mean titer was measured at day eleven chicken (N=60) before vaccination and found 1963.00 ± 143 and 984.16 ± 126.4037 respectively. Of these two titers; Cobb-500 strain was found to be protective (>1000) where Hubbard classic was below protective (<1000) titer level. The two flocks of Cobb-500 and Hubbard classic strains of broiler chickens were vaccinated with intermediate (Bursine-2) and intermediate plus (IBD Blen) vaccine respectively at day twelve and serum was harvested on day twenty six. The mean serum titers were found 131.30 ± 36.04 and 7413.54 ± 569.39 in Cobb-500 and Hubbard classic respectively, where mean titer level of Cobb-500 was below the minimum protective level but Hubbard classic strain was developed 7413.54, protective level. These results were indicating that the maternal derived antibody titer persists above 1000 level hindering the development of antibody titer in vaccinated flocks. However, persistence of MDA titer above 1000 may causes of vaccination failure of IBD vaccine. International Journal of Natural Sciences (2014), 4(2) 22-27